2019
DOI: 10.21608/asjs.2019.177877
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intact Parathyroid Hormone (iPTH) Level as an Early Predictor of Postoperative Hypocalcemia after Total Thyroidectomy for Simple Multi-Nodular Goiter

Abstract: Background: Postoperative hypocalcaemia, secondary to hypoparathyroidism, is the most common complication observed in patients who undergo bilateral thyroid resection. Although hypocalcaemia is self-limiting in most patients and does not require treatment, symptomatic hypocalcemia is of concern. The aim of this research was to identify PTH-24h post-operatively as a simple predictor of early postoperative hypocalcemia following total thyroidectomy for simple multi-nodular goiter.Methods: Fifty patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The effect of calcitonin is expected early, as its half-life is two to 15 minutes (P. Yu et al, 2019). Li et al, (2021), Hamed & Afifi, (2019) and Sharif et al, (2018) showed that there was no significant change in postoperative calcitonin when comparing patients with hypo-or normocalcemia (Hamed & Afifi, 2019;Li, Rogers, & Rehman, 2021;Sharif, Ali, Rahman, Siddique, & Rahman, 2018).…”
Section: Calcitoninmentioning
confidence: 92%
“…The effect of calcitonin is expected early, as its half-life is two to 15 minutes (P. Yu et al, 2019). Li et al, (2021), Hamed & Afifi, (2019) and Sharif et al, (2018) showed that there was no significant change in postoperative calcitonin when comparing patients with hypo-or normocalcemia (Hamed & Afifi, 2019;Li, Rogers, & Rehman, 2021;Sharif, Ali, Rahman, Siddique, & Rahman, 2018).…”
Section: Calcitoninmentioning
confidence: 92%